Consequences of Anabolic Androgenic Steroids Abuse in Males, Sexual Hepatic and Metabolic Perspective - Mohammed, Sura; Anwer, Zina Mudhafar (Iraqi Journal of Pharmaceutical Sciences, 2023)
AbstractBackground: anabolic androgenic steroids (AASs) are becoming increasingly popular between bodybuilders and people who want to enhance their physiques. However, according to the rise of the Internet and laws prohibiting sales of these substances without prescription, the route of obtaining and administration practices have become more and more dangerous.Objective: Anabolic-androgenic steroids represents a group of synthetic testosterone derivatives its play an important role in clinical treatment. These group of drugs are widely abused among the general public to increase lean body weight and improve athletic performance. It has been reported that AAS use can cause many adverse effects. Although there are many related studies, the current study was to review the effect of AAS on serum levels of LH, FSH, prolactin, free testosterone, ALT, AST, T3, T4, TSH, haemoglobin and platelet in bodybuilders using these hormones and compare the results with control group.Method: A 50 body builders were using gym routinely and were using AASs for at least 2 months interviewed and collect blood sample to measure certain lab data and see the effects of AAS on these lab data and compare results with control group who were using gym routinely but never use AAS before.Results: The levels of eight parameters were significantly (P-value< 0.05) different according to the participating groups (AAS users vs control): LH, FSH, Prolactin, ALT, T3, TSH, haemoglobin and platelets. Five of the measured parameters were significantly (P-value< 0.05) lower in the group of AAS users compared to the control (non-user) group: LH, FSH, T3, TSH, and platelets. In contrast, the other three parameters (prolactin, ALT and haemoglobin) were significantly (P-value< 0.05) higher in the AAS user group compared to control group.Conclusion: the anabolic androgenic steroids had a harmful effect on multi physiological functions leading to hormonal disturbances.